Analisis Pengungkapan Laporan Sosial dan Lingkungan dalam Akuntansi Pertanggungjawaban Sosial Perusahaan (Studi pada Bursa Efek Jakarta) - Rajafi, Lalu Roby; Irianto, Gugus (TEMA, 2007)
This  research is  about  to  analyze  social and environmental disclosure  of industries  in  Indonesia  as part  o f triple  bottom  line reporting in corporate social responsibility accounting with seeing their annual report at year 2005. This research focusses on the analysis of social information disclosure’s form and the analysis of the average differences of disclosure topics among industries groups listed at Jakarta Stock Exchange in the year of 2005. This research uses descriptive method to describe disclosure’s forms applied and the average differences of disclosure topics among industries groups listed at Jakarta Stock Exchange. The annual reports were analyzed using content analysis method with Kruskall Walis’s non-parametric  statistical  test  as  a  tools  to  examine  the  average differences of disclosure topics within these industries groups. Based on the Kruskal Wallis’s non-parametric test conducted, there are some significant differences among company groups in disclose environmental and employment issues, while the disclosure of society issues tend to be illustrated in the same form. Each of this company groups are having a different perception about the disclosure topics they present in their Annual Report.  Consequently,  this  has resulted  a  different  topics  to  be  disclosed:  Agriculture  and Mining emphasize on environtmental issues, Consumer Goods Industry (CGS), Property,  Real  Estate  &  Building  Construction  (PRE&BC),  and Infrastructure,  Utilities  &  Transportation  (IU&T)  are  likely  lean  on employment issues,  while Finance and Trade,  Service & Investment (TSI) emphasize on society issues. This was happened because of the essential differences on company’s activities type, company’s sensitivities, and company’s goals. Key  words: Triple  bottom  line  reporting,  social disclosure, and environmental disclosure